Pengaruh Metode Penilaian Persediaan Terhadap Penentuan Harga Pokok Penjualan (Study kasus pada PT. Dirgantara Pancapersada di Bandar Lampung) - Goenawan GOENAWAN; Alvina Susantolie; Yunus Fiscal (Universitas Bandar Lampung (UBL), 2011)
This study aims to determine whether the company is able to generate a reasonable cost of goods sold in its trading inventory count and also to determine whether the inventory valuation method used by the company in accordance with the conditions of the company. Problems faced by PT. Aerospace Pancapersada is whether there is an influence on the determination of inventory valuation method of sales at PT. Aerospace Pancapersada. The hypothesis is the application of the inventory valuation method used to determine the most reasonable cost of sales at PT. Aerospace Pancapersada is FIFO.The research method used was the literature research and field research. The analytical method used is the method of qualitative and quantitative methods. Qualitative method is a method used to compare the inventory valuation method used by companies with other inventory valuation method. While quantitative methods is the method of analysis to perform calculations using numbers.